2018
DOI: 10.1155/2018/1539678
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Family Nanomaterials: Properties and Potential Applications in Dentistry

Abstract: Graphene family nanomaterials, with superior mechanical, chemical, and biological properties, have grabbed appreciable attention on the path of researches seeking new materials for future biomedical applications. Although potential applications of graphene had been highly reviewed in other fields of medicine, especially for their antibacterial properties and tissue regenerative capacities, in vivo and in vitro studies related to dentistry are very limited. Therefore, based on current knowledge and latest progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 85 publications
0
54
0
Order By: Relevance
“…Graphenebased nanomaterials can interact with cells, supporting their adhesion, migration, proliferation, and differentiation [8,9]. nGO as one the popular graphene derivatives can induce translation of some crucial intracellular protein and promote proliferation and differentiation of bone-producing cells and help bone formation [10]. The capability of nGO for bone formation was denoted by Nishida et al in an ex vivo animal study and showed that it is fivefold more potent than the collagen scaffold [11].…”
Section: Introductionmentioning
confidence: 99%
“…Graphenebased nanomaterials can interact with cells, supporting their adhesion, migration, proliferation, and differentiation [8,9]. nGO as one the popular graphene derivatives can induce translation of some crucial intracellular protein and promote proliferation and differentiation of bone-producing cells and help bone formation [10]. The capability of nGO for bone formation was denoted by Nishida et al in an ex vivo animal study and showed that it is fivefold more potent than the collagen scaffold [11].…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted to find a way to improve antibacterial behavior of PMMA and α by incorporation of GO. Nano graphene oxide was selected for its known antimicrobial and highly physical properties [3,[28][29][30][31]. Chemical cure PMMA was selected to avoid thermal damage to the GO during other curing methods [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of nanomaterials, such as graphene and nanotubes, the biocompatibility depends on several factors such as size, purity, shape and number of sharp edges, as it is difficult to assess the general arguments [ 206 , 207 ]. The studies focused on the toxicity of oral applications are limited [ 208 ]. Olteanu et al [ 209 ] performed a study to evaluate the toxicity of graphene-based materials on human dental follicle stem cells.…”
Section: Nanorods Nanowires and Nanotubesmentioning
confidence: 99%